Analysis of anaerobic and aerobic capacity of Safin Pati Sport School Football Academy students - Anam, Khoiril; Indardi, Nanang; Aprilia Nur Azmi, Dina; Latino, Francesca; Tafuri, Francesco (Sepakbola, 2024)
An early approach can be taken to develop youth soccer through the Soccer Academy. The purpose of this study was to analyze the chronic response of the training program to the anaerobic and aerobic capacity of SPSS football academy students. The population in this study was all SPSS soccer academy students, while the sample was 28 students. The sampling technique used in this study was purposive, using inclusion and exclusion criteria. The instruments used in this study were 1) a Running-based Anaerobic Sprint Test (RAST) to measure the level of anaerobic capacity and 2) a Multistage Fitness Test (MFT) to measure the level of aerobic capacity. The results of the RAST said that the anaerobic endurance of 15-year-old SPSS soccer students was “Good,” with an average value of 3.78. Then, the results of the MFT on 15-year-old SPSS soccer students were categorized as “Fair” with an average value of 41.3. The conclusion of this study shows that anaerobic ability in 15-year-old SPSS students is categorized as good, while aerobic ability in 15-year-old SPSS students is categorized as sufficient.